Providing Health Education Salt Dietary to Hypertension Patients - Muzakkir, Muzakkir; Husaeni, Hermin; Muzdalia, Ika; Mutmainna, Amriati; Maharja, Rizky (Sarana Ilmu Indonesia (salnesia), 2023)
Hypertension is still a big health problem. It needs treatment in other forms besides medication, namely increasing understanding regarding salt or natrium consumption. Providing information can be done with various approaches, one of which is by using the health education method. The purpose of this study was to determine the effect of providing health education on salt dietary on hypertensive patients in Majene Regency. This research was an experimental research with a One-group pre-post test design with a sample of 32 subjects who met the inclusion criteria. This study used the wilcoxon signed rank test with a significance level of α< 0,05. The results of this study indicated that after conducting health education, most of the subjects experienced increased knowledge about dietary salt through the provision of health education information. There were differences in knowledge about the Salt diet before and after being given health education with a p-value of 0,003. Based on the results of this study, researchers recommend that nurses master several learning methods in implementing health education. Maintain the BPJS health prolanis community as a forum for communication with the same problem and become a medium for providing mutual support in improving the quality of life for people with hypertension. Nurses should continue to respect the patient's salt consumption habits slowly. Structured and scheduled in changing the client's salt consumption habits.